A Wavelet-Based Data Reduction Approach for Sensor-Rich Ubiquitous Systems - Valéria, Olga; Ribeiro, Anderson; Leal, Liliam; Lemos, Marcus; Carvalho, Carlos; B. Filho, José; Agoulmine, Nazim (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2014: Anais do VI Simpósio Brasileiro de Computação Ubíqua e Pervasiva, 2014)
Sensor-rich ubiquitous systems require continuous monitoring platforms for instantaneously providing context-aware services. These sensor-based monitoring platforms generate a large amount of discrete and waveform data, resulting in a high energy expenditure while transmitting data. In this scenario, data reduction mechanisms can be applied for saving transmission energy of sensor devices by reducing discrete and waveform data, maximizing the availability and reliability of sensor-rich ubiquitous systems. Adaptive Simple Linear Regression (ASLR) is well suited for reducing discrete data, however, it is required a more efficient data reduction approach for reducing waveform data, such as ECG signal. This paper proposes and evaluates a wavelet-based data reduction approach for reducing waveform data, which was integrated with our context management framework.